Hydrostatic Equation

Hypsometric equation

The hypsometric equation relates the atmospheric pressure ratio to the thickness of an atmospheric layer under the assumptions of constant temperature and gravity. It is derived from the hydrostatic equation and the ideal gas law.

It is expressed as:

h = z_2 - z_1 = frac{R cdot T}{g} cdot ln left [frac{P_1}{P_2} right ]

where:

h = thickness of the layer [m]
z = geopotential height [m]
R = gas constant for dry air
T = temperature in kelvins [K]
g = gravitational acceleration [m/s2]
P = pressure [Pa]

In meteorology P_1 and P_2 are isobaric surfaces and T is the average temperature of the layer between them. In altimetry with the International Standard Atmosphere the hypsometric equation is used to compute pressure at a given geopotential height in isothermal layers in the upper and lower stratosphere.

Derivation

The hydrostatic equation:

P = rho cdot g cdot z

where rho is the density [kg/m3], is used to generate the equation for hydrostatic equilibrium, written in differential form:

dP = - rho cdot g cdot dz.

This is combined with the ideal gas law:

P = rho cdot R cdot T

to eliminate rho:

frac{mathrm{d}P}{P} = frac{-g}{R cdot T} , mathrm{d}z.

This is integrated from z_1 to z_2:

int_{p(z_1)}^{p(z_2)} frac{mathrm{d}P}{P} = int_{z_1}^{z_2}frac{-g}{R cdot T} , mathrm{d}z.

Integration gives:

ln left(frac{P(z_2)}{P(z_1)} right) = frac{-g}{R cdot T} (z_2 - z_1 )

simplifying to:

ln left(frac{P_1}{P_2} right) = frac{g}{R cdot T} (z_2 - z_1 ).

Rearranging:

(z_2 - z_1 ) = frac{R cdot T}{g} ln left(frac{P_1}{P_2} right)

or, eliminating the logarithm:

frac{P_1}{P_2} =e ^ { {g over R cdot T} cdot (z_2 - z_1 )}.

References

Search another word or see Hydrostatic Equationon Dictionary | Thesaurus |Spanish
Copyright © 2014 Dictionary.com, LLC. All rights reserved.
  • Please Login or Sign Up to use the Recent Searches feature